1991
DOI: 10.1093/oxfordjournals.humrep.a137386
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal dependence of pinopode formation at the uterine luminal surface

Abstract: The uterine luminal epithelium during the period of receptivity for nidation displays characteristic protrusions of the apical surface named pinopodes. The effects of oestradiol and progesterone, singly or in combination, on the formation and regression of pinopodes were investigated using scanning electron microscopy. The appearance of pinopodes was found to be strictly progesterone dependent. When given together with progesterone, before the development of pinopodes, high doses of oestradiol (plasma level ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
58
0
6

Year Published

1993
1993
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(68 citation statements)
references
References 0 publications
4
58
0
6
Order By: Relevance
“…In pigs, which also have an epitheliochorial placenta, Dantzer [20] commented on progressive loss of uterine epithelial microvilli and flattening of the apical plasma membrane into regions where uterine and trophoblast membranes ran parallel after which microvilli reformed to establish the mature epitheliochorial placenta and in one other epitheliochorial placenta, that of the marsupial mouse, Roberts and Breed [33] have also found flattening and loss of apical microvilli of uterine epithelial cells at attachment in a reaction they described as very similar to that of rats and mice. In the rhesus monkey, Enders et al [34] showed loss of microvilli and other flattened membrane areas on uterine epithelial cell surfaces at attachment and in humans several workers have pointed out similarities between the behaviour of rodent and human uterine epithelial cell apical plasmalemmas during early pregnancy [35][36][37][38][39] as we shall examine in more detail later. As if to highlight the commonality of these events, in a very different class of animals, apical plasma membrane flattening during early pregnancy has now been reported in viviparous lizards [40].…”
Section: The Apical Plasma Membrane In Other Animalsmentioning
confidence: 81%
“…In pigs, which also have an epitheliochorial placenta, Dantzer [20] commented on progressive loss of uterine epithelial microvilli and flattening of the apical plasma membrane into regions where uterine and trophoblast membranes ran parallel after which microvilli reformed to establish the mature epitheliochorial placenta and in one other epitheliochorial placenta, that of the marsupial mouse, Roberts and Breed [33] have also found flattening and loss of apical microvilli of uterine epithelial cells at attachment in a reaction they described as very similar to that of rats and mice. In the rhesus monkey, Enders et al [34] showed loss of microvilli and other flattened membrane areas on uterine epithelial cell surfaces at attachment and in humans several workers have pointed out similarities between the behaviour of rodent and human uterine epithelial cell apical plasmalemmas during early pregnancy [35][36][37][38][39] as we shall examine in more detail later. As if to highlight the commonality of these events, in a very different class of animals, apical plasma membrane flattening during early pregnancy has now been reported in viviparous lizards [40].…”
Section: The Apical Plasma Membrane In Other Animalsmentioning
confidence: 81%
“…During the postimplantation period, pinopod number decreases rapidly (Singh et al, 1996). This developmental change of pinopods in the uterus is highly progesterone dependent, while administration of high doses of estradiol abolishes the pinopod (Martel et al, 1991), highlighting the similarity of hormonal conditioning for pinopod formation with the attainment of uterine receptivity. Therefore, the appearance of pinopods is a well-defined histological marker for uterine receptivity in rats and mice.…”
Section: Introductionmentioning
confidence: 92%
“…Apical swellings known as uterodomes (or pinopodes) -which appear to be absorptive -grow from the surface of some cells, and microvilli become less regular and shorter (Martel et al, 1991;see poster). The lumen closes around the blastocyst to create an implantation chamber; this requires fluid pinocytosis by epithelial cells, a process that might depend on the epithelial sodium channel ENaC, which is activated downstream of the tyrosine kinase SGK-1 (Ruan et al, 2012;Salker et al, 2011).…”
Section: Epithelium-trophectoderm Interaction In Laboratory Rodentsmentioning
confidence: 99%